Intralesional steroid injection combined with bladder neck incision is efficacious in the treatment of recurrent bladder neck contracture. Issue 1 (8th June 2020) - Mann, Jordan A.; Silverman, Joshua; Westenberg, Andre
Abstract: Objectives: Bladder neck contracture (BNC) is a well‐recognized complication following radical prostatectomy (RP). This problem may recur after failing initial endoscopic management. This study evaluated the efficacy of intralesional steroid injection combined with bladder neck incision (BNI) for recurrent BNC following RP. Methods: Between November 2011 and March 2018, data from all men who underwent BNI and intralesional steroid injection for recurrent BNC from a single regional center were collected. BNC was diagnosed endoscopically and identified as recurrent if having previously failed endoscopic management with BNI alone. Follow up was initially performed at 3 months with an International Prostate Symptom Score and urinary flow rate. Patients were noted to be recurrence‐free when discharged from follow up or after having undergone a continence procedure indicating stability of the contracture. Results: Thirty patients underwent BNI and intralesional steroid injection for recurrent BNC over the study period. All patients had received prior endoscopic incision of BNC without lasting success. Seventy percent (21/30) of patients were recurrence‐free post‐procedure, and this increased to 83.3% (25/30) after a repeat procedure in four patients. All five patients who had previous salvage radiotherapy had their recurrent BNC successfully managed with one BNI and intralesional steroid injection. The mean follow up was 33.4 months (range 7‐75). There were no adverse events recorded. Conclusions: BNI combined with injection of intralesional steroids is a simple, cost‐effective intervention which requires no specialist equipment/skills outside the realm of a general urologist. It is safe and has an excellent success rate.